Biomass production, carbon stock and sequestration potential of prominent agroforestry systems in north-western Himalaya, India - Saleem, Ishrat; Mugloo, J. A.; Pala, Nazir A.; Bhat, G. M.; Masoodi, T. H.; Mughal, A. H.; Baba, Afshan A.; Mehraj, Basira (Frontiers in Forests and Global Change, 2023)
Agroforestry is an age-old practise of integrating farming with practises, preferably on the same unit of land on sustainable basis. There is tremendous scope for Agroforestry because India has achieved self-sufficiency in food production. Now its attention is becoming more focused on the ecological problems and shortage of fuel, fodder and other outputs as well as unemployment. So, agroforestry land use systems offer a better option by serving as carbon sinks and contributing in attaining food safety, subsistence income, and habitat amelioration. The current study was conducted in this context in the south Kashmir area of India with the objective of recognising the capability of various agroforestry systems for biomass estimation and carbon sequestration assessment for mitigating climate variation. The present study entitled “Biomass production, carbon stock and sequestration potential of prominent agroforestry systems in North-western Himalaya, India” was carried out, during 2018–2019. The study site is located between 33° 72’N and 75° 14’E at an altitude ranging from 2,900 to 5,900 M (amsl). Multistage random sampling technique was used for selection of sampled tehsils, blocks, villages and farmers in Anantnag district. The first stage was the random sampling of six tehsils namely Anantnag, Shangus, Kokernag, Dooru, Sallar, and Larnu and blocks per tehsil namely, viz.; Anantnag, Shangus, Sagam, Shahabad, Pahalgam and Larnu. Then four villages within each block like Anantnag (Ruhoo, Dialgam, Wanihama and Donipawa), Shangus (Shangus, Nowgam, Kutheir and Andoora), Sagam (Hiller, Khalhar, Sagam and Bidder), Shahabad (Larkipora, Shankerpora, Nathipora and Bragam), Pahalgam (Yanner, Charigam, Movra and Wahdan) and Larnu (Leesu, Dandipora, Bidhard and Larnu). Ten farmers within each village were selected, thus making a total of 240 farmers, which accounts 25% sampling intensity. Four agroforestry systems including horti-agriculture, agrisilviculture, (boundary planting), agri-horti-silviculture and horti-silvipasture were chosen for the study as the experimental configuration. Maximum biomass was found in horti-silvipastoral contributing 66.55 t ha−1 followed by agri-horti-silviculture as 50.18 t ha−1, horti-agriculture as 36.22 t ha−1 and agri-silviculture as 34.87 t ha−1. The maximum mean biomass of fruit trees (30.54 t ha−1), forest trees (25.19 t ha−1), grass (7.18 t ha−1) during the first cut and 3.64 t ha−1 during the second cut, was calculated in horti-silvipasture system. The overall biomass output of diverse agroforestry systems goes along with the sequence: horti-silvipasture > agri-horti-silviculture > horti-agriculture > boundary plantation, respectively. As a result, estimates of carbon stocks and carbon sequestration for all systems showed the same trend as values for biomass since they are both directly related to the capacity for biomass generation of various plant components. By providing for rural livelihoods and serving as an efficient carbon sink through carbon sequestration, these agroforestry systems in the Himalayas can significantly increase total production and productivity. The results of the current study could have a big impact on how alternative agroforestry systems and tree combinations are chosen for efficient carbon budget management in delicate Himalayan ecosystems.